Bidirectional remodeling of the central auditory system caused by unilateral auditory deprivation - Xinying Ge; Cong Xu; Jinsheng Dai; Mo Zhou; Jinfeng Liu; Ningyu Wang (Frontiers in Neurology, 2024)
Unilateral auditory deprivation (UAD) results in cross-modal reorganization of the auditory cortex (AC), which can impair auditory and cognitive functions and diminish the recovery effect of cochlear implantation. Moreover, the subcortical areas provide extensive ascending projections to the AC. To date, a thorough systematic study of subcortical auditory neural plasticity has not been undertaken. Therefore, this review aims to summarize the current evidence on the bidirectional remodeling of the central auditory system caused by UAD, particularly the changes in subcortical neural plasticity. Lateral changes occur in the cochlear nucleus, lateral superior olive, medial nucleus of the trapezoid body, inferior colliculus, and AC of individuals with UAD. Moreover, asymmetric neural activity becomes less prominent in the higher auditory nuclei, which may be due to cross-projection regulation of the bilateral pathway. As a result, subcortical auditory neural plasticity caused by UAD may contribute to the outcomes of cochlear implantation in patients with single-sided deafness (SSD), and the development of intervention strategies for patients with SSD is crucial. Considering that previous studies have focused predominantly on the neural plasticity of the AC, we believe that bidirectional remodeling of subcortical areas after UAD is also crucial for investigating the mechanisms of interventions.